Pengaruh Faktor Internal terhadap Nilai Perusahaan - Jonathan, Jonathan; Siahaan, Magda (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research examines the factors affecting the firm value of non-financial companies in Indonesia. The independent variables in this study are dividend policy, profitability, firm size, leverage, firm growth, liquidity, and audit committee, while the dependent variable is firm value. This study uses data from non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020. The sample data were tested using a multiple regression model, and the sample selection process used a purposive sampling technique so that a sample of 78 companies was obtained from a sample of 312 data. The results of this study indicate that the variables of profitability, firm size, and leverage positively affect firm value; the dividend policy, firm growth, and audit committee variables hurt firm value, while liquidity variables do not affect firm value.